DIE BESTATTUNG JESU. ÜBERLEGUNGEN AUSGEHEND VON 2 SAM 21,1-14 MIT BLICK AUF MK 15,42-16,1 = THE BURIAL OF JESUS. REFLECTIONS BASED ON 2 SAM 21:1-14 WITH A VIEW TO MARK 15:42-16:1 - Hubmann, Franz-Xaver (Sacra scripta, 2024)
The Markan narrative of the burial of Jesus in Mark 15:42-16:1 will be analyzed in comparison with the Rizpah narrative in 2 Sam 21:1-14. The focus will be on the agency of mourning figures and how they deal with burial rituals. In this way, it can be shown how mourning and the relevant rituals are modified and shaped in the Old Testament text and how this reading can introduce new potential meanings for the Markan text. The focus here is on the mourning behavior and interactions of the figures, also the figure of God.